2010
DOI: 10.1007/s10705-010-9409-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus loss by surface runoff from agricultural field plots with different cropping systems

Abstract: Phosphorus (P) loss from agricultural fields through surface runoff may contribute to the eutrophication of surface waters. The objective of this study was to evaluate surface runoff and P transport from different cropping systems during 2007-2009. The treatments consisted of a control (wheat/fallow) and three double cropping systems: wheat/corn (Zea mays L.), wheat/cotton (Gossypium hirsutum L.), and wheat/soybean [Glycine max (L.) Merr.]. Wheat/ fallow was not fertilized and had no crop planted during the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Plough and root growth would disturb the crust form of the soil, and infiltration capacity changes over a crop cycle (Imeson and Kwaad, 1990;Slattery and Burt, 1996). In the North Huaihe Plain of China, leaf area index (LAI) affecting interception was found to be one of the main factors controlling surface runoff in the experiment plots with bare land, corn, cotton, and soybean (Jiao et al, 2009a(Jiao et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Plough and root growth would disturb the crust form of the soil, and infiltration capacity changes over a crop cycle (Imeson and Kwaad, 1990;Slattery and Burt, 1996). In the North Huaihe Plain of China, leaf area index (LAI) affecting interception was found to be one of the main factors controlling surface runoff in the experiment plots with bare land, corn, cotton, and soybean (Jiao et al, 2009a(Jiao et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…3) and the rate was justified by higher dry matter production of the crops (Table 1). Furthermore, the use of crop rotation also has significant effects on reducing surface runoff, as observed by Jiao et al (2011). These authors found increases in water infiltration into the soil and up to 58 % reduction in runoff volume in a study evaluating different crop rotations.…”
Section: Effect Of Swine Effluent Applications On Available P In Soilmentioning
confidence: 74%
“…In years with higher rainfall, as in the crops of maize (2006/2007) and black oat (2007), the soil remains moist with much of its porosity occupied by water, hindering water infiltration and favoring surface runoff. High soil moisture may result in an increased runoff volume for each event (Jiao et al 2011), as well as an increase in the number of runoff events (Udawatta et al 2006). …”
Section: Effect Of Swine Effluent Applications On Available P In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning dissolved nutrients, model predictions lay within the ranges of values reported in the literature, although closer to the lower values, and varied from about 416–1289 g ha −1 y −1 for dissolved N and 468–793 g ha −1 y −1 for dissolved P (Vuorenmaa et al, ; Hart et al, ; Ramos & Martínez‐Casanovas, ; Udawatta et al, ; Jiao et al, ; Sweeney et al, ). However, the N/P ratio was low compared with average values (Pärn et al, and references therein), owing to the rather high P availability of these soils in the surface layer (Table ).…”
Section: Resultsmentioning
confidence: 99%